A New Objective Parameter in Hydroxychloroquine-Induced Retinal Toxicity Screening Test: Macular Retinal Ganglion Cell-Inner Plexiform Layer Thickness - Mehmet BULUT; Muhammet Kazım EROL; Devrim TOSLAK; Melih AKIDAN; Ebru KAYA BAŞAR; Hasan Fatih ÇAY (Archives of Rheumatology, 2018)
Objectives: This study aims to detect hydroxychloroquine (HCQ)-induced retinal toxicity at an earlier stage through the use of spectral-domain optical coherence tomography device, especially by measuring macular retinal ganglion cell-inner plexiform layer (RGC-IPL) thickness. Patients and methods: In this study, 92 eyes of 46 Caucasian female patients (mean age 53.6±8.1 years; range 32 to 69 years) who were taking HCQ were assigned to group 1, while 80 eyes of 40 age-matched Caucasian female control subjects (mean age 56.1±10.7 years; range 34 to 71 years) were assigned to group 2. RGC-IPL thickness and retinal nerve fiber layer thickness were measured in all subjects by Cirrus high-definition optical coherence tomography model 5000 device using macular cube 512¥128 and optic disc cube 200¥200 protocols. We performed an evaluation to see if there was any difference between the measured values of the groups. The correlation between average RGC-IPL thickness measures and cumulative dose of HCQ and duration of use was analyzed. Results: Retinal ganglion cell-inner plexiform layer of group 1 was found to be statistically thinner than that of group 2 both on average and in all segments (superior, superonasal, inferonasal, inferotemporal and superotemporal) except inferior segment when segmented (p<0.05). Additionally, a statistically significant negative correlation was found between the average RGC-IPL thickness and cumulative dose of HCQ (r= -0.371, p=0.001) as well as the duration of use (r= -0.308, p=0.006). Conclusion: Patients taking HCQ were found to have decreased RGC-IPL thickness at an early stage due to retinal toxicity induced by the drug. We think that measuring the RGC-IPL thickness may become an important objective in HCQ screening tests.